Investigation of tribological properties of nanostructured objects on atomic-smooth surfaces - Vasko, A.A.; Kutsenko, V.Ye.; Marchenko, A.A.; Braun, O.M.; Naumovets, A.G. (Reports of the National Academy of Sciences of Ukraine, 2018)
A fundamentally new method for the study of the friction in a point contact with the help of a pendulum levitated in a magnetic field has been developed and tested. The main advantage of the method is non-destructive regimes of measurements for the ultrathin (e.g., monolayers) lubricant films. The method allows us to provide fast measurements of friction coefficients in regimes of dry friction and in the presence of a lubricant film. Self-assembled monolayers of n-alkanes n-CnH2n+2 (n = 24 tetracosan, and n = 48, octatetracontan) deposited on the atomic-smooth surfaces of highly oriented pyrolytic graphite (HOPG) are used for these purposes. The structure of monolayers is investigated, by using a scanning tunneling microscope (STM) with molecular resolution. The obtained results are explained in the frame of a simple one-dimensional model, which considers n-alkane chain adsorbed on the graphite substrate. Using this model, we have found that the sliding force acting on an n-alkane molecule depends on the molecular length in non-monotonic manner.